IMPLEMENTASI ENTERPRISE RESOURCE PLANNING (ERP) PENGELOLAAN SPARE PART PADA PT. ABADI PRATAMA INDUSTRI - Rizal, Rizalzaelani; Patandung, Heri; Supendi, Supendi; Suzanto, Boy (E-Jurnal Akuntansi TSM, 2024)
The focus of this research is to determine how to implement Enterprise Resource Planning (ERP) Spare Part Management at PT. Abadi Pratama Industri. This research uses descriptive research type. The data sources used in this research are primary and secondary data. To obtain information that is relevant to the problems discussed, the author uses information gathering methods such as observation, interviews, documentation and literature. Based on the results of the Spare Part Management research before using the Enterprise Resource Planning (ERP) network procedures on cash disbursement are still carried out by the same function, the related documents are incomplete and made manually and the financial statements made are not separate and there are no document numbering. Spare Part Management after using the Enterprise Resource Planning (ERP) network procedures for cash disbursement carried out by different functions, the related documents are in accordance with the procedures and are created automatically based on the system and the financial reports that have been made are separate and there are document numbe rs generated by the system ERP. ERP implementation of spare part management at PT. Abadi Pratama Industri as a whole shows better results and is in accordance with the procedure.